Peranan Penyuluh Pertanian Lapangan pada Masyarakat di Era Modern - Bambang Eka Saputra; Muchamad Triyanto; Lalu Murdi; M. Shulhan Hadi; Hary Murcahyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to describe the role of Field Agricultural Extension (PPL) in improving the welfare of farming communities and to determine the inhibiting factors of agricultural extension in modern times. The research method uses a descriptive qualitative approach. The data are in the form of direct observation, interview results, and documentation results. Collecting data obtained from respondents. The analysis uses descriptive analysis and historical approach. The results of this study indicate that Field Agricultural Extension (PPL) plays a very important role in the socio-economic field in modern times. The inhibiting factors for agricultural extension are: lack of facilities and infrastructure, namely mobility, experimental land, agricultural extension equipment, funding, and social problems. The conclusion of this research is that Field Agricultural Extension (PPL) plays an active role even though there are still many obstacles. Keywords: Agricultural Extension, Farmer, Modern Era